Modelagem e filtragem de distorções estáticas em levantamentos de dipolos contínuos - RÉGIS, Cícero Roberto Teixeira (Universidade Federal do Pará, 2014)
Static distortions are a serius problem to the magnetotelluric method and many atempts to eliminate or to minimize them in the MT data have been tried with more or less success. This work is an overview on a new technique that deals with this problem, the EMAP method, witch is a modification of the traditional MT method in witch the measures of the electric field are made in a continuous line of dipoles equally spaced, and the data so obtained are filtered with a spatial low-pass, frequency dependent digital filter. This work is composed of two main parts, the numerical simulation of electric field data distorted by the static shift and the aplication of the spatial low-pass filter to minimize the static shift. In the first part, we use the finite elements method to simulate the response of the electric dipole witch actually makes the electric field measurements; in the second part, we aply the Hanning window as the spatial filter to treat the data.